Antimicrobial activity of spironolactone against Cutibacterium acnes - Ilić, Dušan; Cvetković, Maja; Grigorov, Maja; Mladenović-Antić, Snežana; Ćirić, Vojislav; Pavlović, Dragana; Tasić-Kostov, Marija (Archives of Pharmacy, 2022)
Spironolactone (SP) is being used as off-label systemic and topical acne therapy, due to its anti-androgen potential. Our previous study confirmed the safety of topical 5% SP preparations. Cutibacterium acnes (C. acnes) is an anaerobic Gram-positive bacillus that leads to severe acne skin lesions. Although there were some assumptions, there are currently no data on antimicrobial activity of SP. In this regard, we aimed to investigate the potential activity of SP against C. acnes. Two different samples were tested: 5% SP DMSO solution and 5% SP topical emulsion stabilized with alkyl polyglucoside (APG) sugar emulsifier. Minimum inhibitory concentration (MIC) was determined by a microwell dilution method according to the recommendations of the National Committee for Clinical Laboratory Standards. Vancomycin was used as positive, while DMSO was negative control. Both tested samples showed antimicrobial potential against C. acnes (ATCC 6919). The MIC values were 1.56 mg/g for 5% SP solution and 0.078 mg/g for 5% SP emulsion. These results showed that the antimicrobial activity of SP was better from the emulsion, which could indicate that APG emulsion vehicle can enhance antimicrobial activity of SP. DMSO showed minor activity against tested microbial strain confirming that antimicrobial activity depended on SP. On the other side, commercial antimicrobial drug vancomycin exhibited obviously higher antimicrobial activity than SP, as expected. SP per se and after incorporation into APG emulsion vehicle showed satisfactory antimicrobial activity against C. acnes. This supports its use in acne therapy, particularly regarding topical treatment of this common skin disease.